A novel cluster of rotavirus-associated neurological symptoms. (4th April 2011) - Jackson, C; Bryant, P; Day, T G
Abstract : Aim: To describe a cluster of children infected with rotavirus presenting with neurological symptoms and discuss the potential clinical implications. Methods and results: Over a 4-week period, four children presented to our hospital with various neurological symptoms and were subsequently found to have rotavirus in their stool (summarised in table 1 ). All four children made a complete recovery, and were well when reviewed at 6 weeks. Conclusion: Rotavirus infection in children in the resource-rich countries is usually benign but complications are rarely reported. This is the first reported cluster of children with neurological symptoms associated with rotavirus gastrointestinal infection. Potential mechanisms for how rotavirus causes its rare neurological complications are discussed. Although the neurological manifestations of rotavirus infection are rare, given the extremely high incidence of rotavirus infection this case series has important clinical implications. Three of the four children described here were started on aciclovir for possible encephalitis. Although this should remain standard practice as diarrhoea is a common childhood symptom, we suggest that in a child with neurological symptoms who improves rapidly, detection of rotavirus in the stool may assist clinicians in the decision to stop aciclovir early, especially if there is no CSF available.